'You Felt Disembodied': Reconfiguring Vulnerabilities Through Metalepsis in Harry Parker's Anatomy of A Soldier. (7th June 2021) - Marcellin, Katia
Abstract: Harry Parker's first novel, Anatomy of a Soldier (2016), is a trauma narrative intermingling several timelines and told from the perspectives of forty-four object-narrators. This produces temporal and focal shifts in the narrative, which occur through stylistic metalepsis, that is, through discrepancies that blur the boundaries between causes and effects or between entities. This article proposes to examine how the use of metalepsis in this novel reconfigures the representation of trauma. Through metalepsis, Parker's novel seeks to come as close as possible to the reality of the traumatized psyche, to materialize the space left blank by the shattering force of the traumatic event. Yet, beyond that representational issue, metalepsis also fulfils an ethical function in the novel: by performing rather than showing the workings of trauma, the narrative produces, and includes the reader in, a fragile yet tangible community of shared vulnerabilities.